Distribuição Microrregional e Susceptibilidade Antimicrobiana de Escherichia Coli Patogênica Isoladas de Bovinos no Município de Araguaína-TO. - Maciel, Karina Almeida (Universidade Federal do Tocantins, 2023)
Bacterial resistance is a global health problem, where Escherichia coli (E. coli) is often involved in multidrug resistance to clinically important antibiotics for treatment in humans, and this bacterial species is often used as an indicator of resistance in bacterial products. animal origin, as this is one of the main routes of spread of antibiotic resistance to humans according to the World Health Organization (WHO). In addition, cattle are known to be asymptomatic reservoirs and potential disseminators of O157: H7, a serotype of worldwide importance for triggering severe renal and neurological complications in humans. Similarly, E. coli enteropathogens serogroup also stands out as being a major cause of childhood diarrhea worldwide, however, there is little epidemiological data on its frequency in cattle intended for human consumption. Thus, the aim of the present study was to determine the susceptibility to antibiotics routinely used in health care by means of disc-diffusion microbial susceptibility testing, as well as to identify O157: H7, EPEC (A, B and C) and EIEC seropathotypes. (A and B) and search for the eae and rfb O157: H7 gene in 259 fecal isolated E. coli samples and ruminal content of 323 cattle slaughtered under State Inspection in Araguaína-To. In total, 259 isolates of E. coli were obtained, 186 isolates of feces and 73 isolates of ruminal content. Regarding serology, 149 of the isolates were positive against O157: H7 and EPEC antisera, 22 for O157: H7 and 127 for EPEC (A, B and C), there was a higher positive rate for serogroup B. 110 negative samples were obtained from the antisera. And as for gene research, 7 samples out of 259 were positive for the eae gene and none for the rfb O157: H7 gene. Overall, sulfonamide was the antibiotic with the highest resistance, followed by florfenicol, gentamicin, enrofloxacin and amoxicillin + clavulanic acid, doxycycline and cefepime. By analyzing the different biological materials investigated, stool isolates were resistant to four antibiotics and those of rumen content to eight, and when comparing the multidrug resistance profile stool isolates were resistant to ciprofloxacin and those of rumen content to chloramphenicol, enrofloxacin, cefepime and doxycycline. O157: H7 antiserum positive isolates were multidrug resistant to 9 antibiotics, and EPEC antisera positive isolates (A, B and C) were multidrug resistant to 2 antibiotics. The isolates positive for the eae gene showed multidrug resistance to 6 antibiotics. In our study, negative samples against the antisera tested showed multidrug resistance profile to 5 antibiotics. The multidrug resistance profile found in this study suggests the need for greater caution in the use of antibiotics for cattle in the region studied, given the high resistance rates obtained and the concomitant use of some clinically important antibiotics in humans, and the technique of Direct agglutination used suggest cattle as a potential reservoir of the EPEC category.